Model Pembelajaran Kooperatif Tari Kreasi Lampung Dalam Ekstrakurikuler SMA Negeri 2 Tegineneng - Putri Sheli Yualita; I Wayan Mustika; Riyan Hidayatullah (Jurnal Seni dan Pembelajaran, 2017)
This research aims to describe the creativity of learners in creating a new dance movement using STAD type cooperative learning model. This research is a qualitative descriptive research. The sources of data obtained in this study are nine students who follow extracurricular activities in the school. Techniques used to collect the data are non-participant observation, interview, documentation, and practical test. The STAD type cooperative model is applied to the Lampung creation dance learning from the first meeting to the final meeting. The steps of using cooperative learning model are to manage students in groups, from nine students into two groups, to plan the task of looking for exploration stage and the formation of Lampung creation dance movements. Assessment is given through three aspects: wiraga (dance movements formation), wirasa (appreciation) and floor pattern.Penelitian ini bertujuan untuk mendeskripsikan tentang kreativitas peserta didik dalam menciptakan gerak tari baru dengan menggunakan model pembelajaran kooperatif tipe STAD. Penelitian ini merupakan penelitian deskriptif kualitatif. Sumber data yang diperoleh dalam penelitian ini adalah 9 siswi yang mengikuti kegiatan ekstrakurikuler di sekolah tersebut. Teknik yang digunakan untuk mengumpulkan data adalah observasi non partisipan, wawancara, dokumentasi, dan tes prkatik. Model pembelajaran kooperatif adalah strategi pembelajaran yang melibatkan partisipasi peserta didik dalam satu kelompok kecil untuk saling berinteraksi. Penilaian diberikan melalui tiga aspek yaitu wiraga (pembentukan gerak tari), wirasa (penghayatan) dan pola lantai.Kata kunci : model pembelajaran kooperatif, pengembangan gerak tari, kreativitas.